Pelanggaran Prinsip Kesantunan Berbahasa dalam Novel Bergenre Perempuan Tertindas dalam Novel Perempuan di Titik Nol dan Novel Cantik Itu Luka - Fatma, Annisa; Agustina, Agustina (Persona: Kajian Bahasa dan Sastra, 2023)
The purpose of this research is to explain the forms of violations of politeness principles that occur in oppressed women genre novels and explain the causes of violations of politeness principles in oppressed genre novels in the novel Beauty is Wounds and the novel women at point Zero. This research uses mixed methods, namely combining qualitative and quantitative methods. The object of this research is all the dialogue of the characters in the novel Beauty is Wounds and the novel women at point Zero. This research uses mixed methods, namely combining qualitative and quantitative methods. The object of this research is all the dialogue of the characters in the novel Beauty is Wounds and the novel women at point Zero. Data collection in this research was a free listening and note taking technique. The research results found 93 data. (1) violations of the principles of language politeness in oppressed women's novels in the women's novels in women at Point Zero and the beauty is wounds consist of 93 data consisting of six maxim violations, namely, violations of the maxim of wisdom, violations of the maxim of generosity, violations of the maxim of praise, violations of the maxim of humility , violation of the maxim of agreement, and violation of the maxim of sympathy, (2) the causes of violations of the principles of language politeness in oppressed women's novels which consist of five factors that cause violations, namely, direct criticism, emotional encouragement, protectiveness of opinions, cornering, and accusation. This research is useful both theoretically and practically. Theoretically, this can provide additional information regarding understanding violations of linguistic politeness maxims and forms of politeness violations in Latin-like languages. In practice, the results of this research can be used in the world of education as a relevant reference/source for further research by pragmatic researchers, especially in cases of violations of linguistic politeness maxims.